(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In this article, we will try to understand the problem of preparing social studies students for inclusive education, what is needed for this and how to help the student body in their development. Also, we list some of the problems that teachers face when adopting an inclusive approach in schools and determine their solutions. Psychological preparation for inclusive education implies the formation of a certain position based on the following values and beliefs.